PENGARUH INTERNET FINANCIAL REPORTING, TINGKATPENGUNGKAPAN DAN KETEPATAN WAKTU PENYAMPAIAN INFORMASI KEUANGAN WEBSITE TERHADAP HARGA SAHAM: Studi Empiris Pada Perusahaan Yang Listing di JII Periode 2008-2012 - Setyarini, Dini; Praptitorini S, Mirna Dyah (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2014)
This study aims to analyze the influence of Internet FinancialReporting (IFR) , Level Disclosure and Timeliness (Timelines)Submission of Financial Information Website On The Stock Market.Sample in this study consisted of 70 companies listed in the JakartaIslamic Index (JII) from 2008-2012. Data analysis uses multipleregression analysis.The results of hypothesis testing showed that theIFR has a significant influence on the abnormal stock returns, thelevel of disclosure has negative effect on abnormal stock returns andtimeliness has no significant effect on abnormal stock returns.